A Kinetic‐Thermodynamic Study of the Effect of the Cultivar/Total Phenols on the Oxidative Stability of Olive Oils. (22nd March 2020) - Veloso, Ana C.A.; Rodrigues, Nuno; Ouarouer, Yosra; Zaghdoudi, Khalil; Pereira, José A.; Peres, António M.
Abstract: Physicochemical parameters, total phenols contents (TPC), and oxidative stabilities at 120–160 °C were evaluated for two monovarietal (Arbequina and Cobrançosa cultivars, cvs .) and one blend extra‐virgin olive oil, confirming the label quality grade and allowing grouping them according to the different TPC (TPC = 88 ± 7, 112 ± 6 and 144 ± 4 mg CAE/kg, for cv . Arbequina, blend and cv . Cobrançosa oils, respectively). The lipid oxidation rate increased with the decrease of the TPC, being Cobrançosa oils (higher TPC) more thermally stable. Kinetic‐thermodynamic parameters were determined using the activated complex/transition‐state theory and the values did not significantly differ for Cobrançosa and blend oils, which had the highest TPC, suggesting a hypothetically threshold saturation of the beneficial effect. Cobrançosa oils had a significant more negative temperature coefficient, higher temperature acceleration factor, greater activation energy and frequency factor, higher positive enthalpy of activation, lower negative entropy of activation, and greater positive Gibbs free energy of activation, probably due to the higher TPC. The results confirmed that lipid oxidation was a nonspontaneous, endothermic, and endergonic process with activated formed complexes structurally more ordered than the reactants. A negative deviation from the Arrhenius behavior was observed for all oils being the super‐Arrhenius behavior more marked for Arbequina oils that had the lowest TPC. Finally, the kinetic‐thermodynamic parameters allowed classifying oils according to the binomial olive cultivar/total phenols level, being the temperature acceleration factor and the Gibbs free energy of activation at 160 °C the most powerful discriminating parameters.